Bioethical Issues in Healthcare - Clark, Peter A. (IntechOpen, 2022)
This book examines the challenges in bioethics from medical, ethical, legal, and industrial perspectives. A critical exchange of ideas from professionals in interdisciplinary fields allows all people to learn and benefit from their far-reaching insights gained through personal and professional experiences in the fields of medicine and research. Examining these complex issues, ranging from brain-computer interfaces to disabilities in health care to the determination of death to safe injection sites, presents viable paradigms for all healthcare professionals who are being confronted with these issues today and in the future. The more we face these challenges directly, examine them critically, analyze them thoroughly, and debate them enthusiastically the more knowledge will be gained and hopefully more lives will be saved.